2018 30th International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD) 2018
DOI: 10.1109/cahpc.2018.8645903
|View full text |Cite
|
Sign up to set email alerts
|

Phase-Based Data Placement Scheme for Heterogeneous Memory Systems

Abstract: Heterogeneous memory systems are equipped with two or more types of memories, which work in tandem to complement the capabilities of each other. The multiple memories can vary in latency, bandwidth and capacity characteristics across systems and they come in various configurations that can be managed by the programmer. This introduces an added programming complexity for the programmer. In this paper, we present a dynamic phase-based data placement scheme to assist the programmer in making decisions about progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 23 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…Dulloor et al [7] also demonstrated that a careful placement of data-structures across memory tiers is necessary to incorporate NVM into the processor memory hierarchy. Plenty of methodology has been proposed for this purpose, including profiling based on sampling of hardware counters [21], [35], runtime-assisted profiling [3], or object-level placement granularity [8], [29] versus its page-level counterpart [39], [40]. Wen et al [38] proposed ProfDP, a differential profiling mechanism (requiring three profiling runs) to estimate per-object latency and bandwidth sensitivity, and decide a priority to guide placement decisions.…”
Section: Related Workmentioning
confidence: 99%
“…Dulloor et al [7] also demonstrated that a careful placement of data-structures across memory tiers is necessary to incorporate NVM into the processor memory hierarchy. Plenty of methodology has been proposed for this purpose, including profiling based on sampling of hardware counters [21], [35], runtime-assisted profiling [3], or object-level placement granularity [8], [29] versus its page-level counterpart [39], [40]. Wen et al [38] proposed ProfDP, a differential profiling mechanism (requiring three profiling runs) to estimate per-object latency and bandwidth sensitivity, and decide a priority to guide placement decisions.…”
Section: Related Workmentioning
confidence: 99%
“…Some other projects employ application-level tools to tag and profile certain data structures, and then use heuristic models to assign objects to the appropriate tier [2,4,18,42,63,66]. While these efforts demonstrate that application guidance can be useful for certain usage scenarios, they require manual source code modifications or expensive online detection to attach recommendations to data objects.…”
Section: Software-directed Heterogeneous Memory Managementmentioning
confidence: 99%